Laminated Object Manufacturing of Metal Foil - Process Chain and System Technology - Prechtl, Martin; Otto, Andreas; Geiger, Manfred (Advanced Manufacturing Systems and Technology: Proceedings of the 7th International Conference, 2005)
Laminated Object Manufacturing of metal foil as an automated two-step procedure is a novel technology for additive manufacturing of massive three-dimensional parts. It enables for example the production of technical tools like moulds. The great advantage hereby is the high accuracy in combination with a high stability of the resulting tools. A laser system for the automated stacking of metal foil contours has been developed. The stacking procedure is realised by a combination of layer fixing and contour generation with a laser beam. But the stability of the produced foil stack is insufficient for most kind of application. Therefore a second step to enhance the mechanical properties of the part is necessary. This can for example be realised by high temperature brazing or diffusion welding. In this paper the laser system for the automated stacking of metal foil contours is described as well as the required preparation of the layer data. Further on some results of investigations on the sub-processes layer fixing, counter generation and final joining are shown.
LFT Import::2019-08-05 (1127)
Keywords: Diffusion welding; Laser material processing; Rapid tooling